Il progetto AI-RON MAN: come l’unione di dati satellitari ed Intelligenza Artificiale ci aiuterà a proteggere le infrastrutture dagli incendi (GEOmedia, 2023)
Climate change has significantly increased forestfire risk across EU, threatening our criticalinfrastructures providing essential for services,e.g. mobile telecommunication. AI-RON MANproject aims to deliver a tool to dynamically predictwildfire risk in areas where such infrastructuresare located, supporting first responders topreventively intervene and avoiding service disruption.The tool will be based on AI techniquesthat enable the exploitation of existing historicaldatasets (including satellite images from Copernicus)to forecast future wildfire likelihood andexpected severity.